The Service Quality of Telemedicine in Indonesia During Covid-19: a Survey within Jakarta Area - Dodi Permadi; Richardus Eko Indrajit; Handri Santoso; Erick Dazki (JTKSI (Jurnal Teknologi Komputer dan Sistem Informasi), 2022)
During the Covid-19 pandemic, many countries had different strategies to stop the spread of the novel virus and help patients. Challenges arise from the character of the virus that needs social distancing to prevent and stop transmission. It brings us to the era of health technologies faster than it should. In this case, a telemedicine service is part of the strategy to reach out to the patient while keeping the bed occupancy ratio in the hospital low because many have light symptoms. But how the service quality of telemedicine and what to expect from its service, demands an analysis for further improvement. This paper using survey method with certain criteria to give clear understanding of the telemedicine service and what should improve.